Ilmu Pendidikan Islam bagi Anak Difabel - Firsya Yunia Amanda; Nur Hasnah; Fathimah Raniyah; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education fairness being the important thing to note in this nation. The House should not be disabled again getting marginalized place. They have the same right to a decent education